Implementation of 8E Learning Cycle Model with Instagram to Overcome Student Misconceptions in Buffer Solution Material - Muhammad Rizal; Rusmansyah Rusmansyah; Rusliana Sari (Jurnal Tadris Kimiya, 2022)
This study aims to determine the effectiveness of applying the 8E learning cycle model with Instagram to overcome student misconceptions in Buffer Solution material. In particular, this study analyzed the differences between the 8E learning cycle model and the online (conventional) expository model with Instagramin overcoming student misconceptions about buffer solution materials. This research method is a quasi-experiment with a non-equivalent control group design. Data collection used a three-tier multiple choice test technique and five experts' validated student response questionnaires. The sampling technique uses purposive sampling. Data analysis techniques use descriptive and inferential analysis of t-tests. The t-test is used to analyze the difference in concept understanding learning outcomes between the experimental and control classes to determine the effectiveness of the 8E learning cycle model. The results showed there were significant differences in concept understanding and misconceptions between experimental class students and control class students (0.00<0.05). Experimental class concept understanding was higher (43.62%) than the control class (28.95%), and experimental class misconception was lower (40.76%) than the control class (47.81%). From these data, it can be concluded that the application of the 8E learning cycle model is more effective than the expository (conventional) online model in overcoming misconceptions in buffer solution materials. The 8E learning cycle model can be an alternative to overcome misconceptions and improve students' understanding of concepts in buffer solution materials.